Chirality induction and chiron approaches to enantioselective total synthesis of alpha-lipoic acid - Chavan, Subhash P.; Pawar, Kailash P.; Praveen, Ch; Patil, Niteen B. (Tetrahedron, 2015)
An efficient, short and convenient asymmetric synthesis of (R)-(+)-lipoic acid in seven steps from chiral hydroxy aldehyde with 32.5% overall yield is described. Synthesis of S and R enantiomers of a-lipoic acid from cis-1,4-butene diol derived chiral lactone is reported with 34 % overall yield. The present synthesis involves use of simple reaction conditions making it a convenient synthesis. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Chiral pool; Chirality induction; enantioselective; Lipoic acid; sharpless asymmetric dihydroxylation